Война и мир - Толстой Лев Николаевич (Мировая классика, 2023)
Экземпляры: ЦБ (20230529) / Инвентарный номер: 59707 / Цена: 163.00 / Сис.шифр: 84(2=411.2) / Авт.знак: Т 53 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)-44